Effects of ClpP protease on biofilm formation of Enterococcus faecalis (Journal of Applied Oral Science, 2021)
Enterococcus faecalis (E. faecalis), one of the main pathogens responsible for refractory periapical periodontitis and nosocomial infections, exhibits markedly higher pathogenicity in biofilms. Objectives: Studies have shown that caseinolytic protease P (ClpP) is involved in biofilm formation. However, to date, few studies have investigated the role of ClpP in the survival of E. faecalis, and in enhancing biofilm formation. Therefore, we investigated the role of ClpP in the formation of E. faecalis biofilms. Methodology: In our study, we used homologous recombination to construct clpP deleted and clpP complement strains of E. faecalis ATCC 29212. A viable colony counting method was used to analyze the growth patterns of E. faecalis. Crystal violet staining (CV) and confocal scanning laser microscopy (CLSM) were used to characterize biofilm mass formation and scanning electron microscopy (SEM) was used to observe the biofilm microstructure. Data was statistically analyzed via Student’s t-test or one-way analysis of variance (ANOVA). Results: The results exhibited altered growth patterns for the clpP deletion strains and depleted polysaccharide matrix, resulting in reduced biofilm formation capacity compared to the standard strains. Moreover, ClpP was observed to increase bioﬁlm formation in E. faecalis. Conclusion: Our study shows that ClpP can increase bioﬁlm formation in E. faecalis and emphasizes the importance of ClpP as a potential target against E. faecalis.